Comparison of the Effectiveness of Mindfulness-Based Stress Reduction Training and Acceptance and Commitment Therapy on Affective Control in Pregnant Women in Ilam City in 2019 - Mohammadzadeh, Marzieh; Mami, Shahram; Ahmadi, Vahid; Rashidian, Tayebeh (Applied Family Therapy Journal (AFTJ), 2024)
Objective: This study aims to compare the effectiveness of Mindfulness-Based Stress Reduction (MBSR) and Acceptance and Commitment Therapy (ACT) on affective control in pregnant women.Methods: A randomized controlled trial was conducted with 45 pregnant women from Ilam, Iran, who were randomly assigned to one of three groups: MBSR, ACT, or control. Participants in the experimental groups underwent 8 weekly group sessions of either MBSR or ACT, while the control group received no intervention. Affective control was measured using the Affective Control Scale, which includes subscales for anger, anxiety, depression, and positive affect. Pre-test and post-test assessments were administered to all groups, and data were analyzed using ANCOVA to compare the effects of the interventions across groups.Findings: The results indicated significant improvements in affective control for both MBSR and ACT groups compared to the control group. The ANCOVA showed significant effects for both MBSR and ACT in reducing anxiety, improving positive affect, and regulating anger, with no significant difference between the two experimental groups. The control group showed no significant changes in any of the emotional regulation variables. Both experimental groups demonstrated a large effect size for affective control (η² = 0.53), with smaller but significant effects on anxiety and positive affect (η² = 0.19 and η² = 0.17, respectively).Conclusion: Both MBSR and ACT were effective in improving affective control and emotional regulation in pregnant women, with similar outcomes for both interventions. These findings suggest that both therapies could be useful tools for managing stress and enhancing emotional well-being during pregnancy.